Predictors of Intensive Care Unit Admission in Red Code Patients in the Emergency Department: A Single-Center Retrospective Observational Study - Boğa, Erkan (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Red code patients in the emergency department require urgent medicalcare because they present with life-threatening medical conditions. Optimal resource distribution together with better patient results depends on finding ICU admission predictors for critical patients who need immediate medica treatment. Aims: This research evaluated both clinical and biochemical factors along with demographic characteristics which determine ICU admission for red code patients at the Esenyurt Necmi Kadıoğlu State Hospital Emergency Medicine Department from 2023 to 2024. Methods: The research conducted a single-center retrospective observational study that used 5,000 red code patient data documented by the hospital information management system during January 2023 to December 2024. The research team evaluated patient demographics and vital signs and laboratory parameters and clinical outcomes from 5,000 patients who had an average age of 64.2 ± 18.5 years and consisted of 52% male patients. The study used univariate analysis together with multivariate logistic regression analysis to identify ICU admission predictors. The ROC curve analysis evaluated model predictive power by presenting AUC with confidence interval values. Results: The analysis included 4,880 patients who fulfilled the study criteria from the total 5,000 screened patients. ICU admission occurred in 30.1% of the total patients. The univariate analysis showed that CRP and WBC and lactate measurements and low blood pressure (systolic BP <90 mmHg) were factors associated with ICU admission. The multivariate analysis confirmed CRP (OR: 1.0007 per mg/L increase, 95% CI: 1.00001–1.0014, p = 0.043), WBC (OR: 1.017 per unit increase, 95% CI: 1.003–1.032, p = 0.014) and hypotension (OR: 2.48, 95% CI: 1.96–3.13, p < 0.001) as independent risk factors. The model demonstrated an AUC of 0.74 (95% CI: 0.71–0.77) which indicates moderate predictive accuracy.Research findings showed that both CRP and lactate demonstrated increased strength in predicting ICU admission when testing patients with septic conditions. Conclusion: The combination of elevated CRP levels with WBC count and high lactate values and hypotension functions as predictive indicators for ICU admission in patients who receive a red code. The available parameters serve as useful risk assessment tools during the first stages of patient care. The implementation of these parameters through triage protocols will improve both emergency clinical decisions and ICU resource management.